FRI0518 A Loss of Telocytes Accompanies Fibrosis of Multiple Organs in Systemic Sclerosis. (10th June 2014) - Manetti, M.; Rosa, I.; Messerini, L.; Guiducci, S.; Matucci-Cerinic, M.; Ibba-Manneschi, L.
Abstract : Background: Telocytes are a distinct population of stromal (interstitial) cells recently identified in a variety of tissues and organs. By their extremely long cytoplasmic processes telocytes form a three-dimensional network that functions as a scaffold to define the correct organization of tissues/organs during pre-natal life or their repair/renewal in post-natal life. According to their specific locations within different organs, telocytes may participate in intercellular signaling, either by cell-to-cell contacts or by secreting paracrine signaling molecules, immune surveillance, neurotransmission, and tissue regeneration by forming tandem cell structures with stem cell niches. Recently, we have shown that telocytes display severe ultrastructural damages suggestive of ischaemia-induced cell degeneration and are progressively lost from the clinically affected skin of systemic sclerosis (SSc) patients. Objectives: To investigate the presence and distribution of telocytes in the internal organs of SSc patients. Methods: Archival paraffin-embedded samples of gastric wall, left ventricular myocardium and lung from SSc patients and controls were collected. Tissue sections were stained with Masson's trichrome to detect fibrosis. Telocytes were studied on tissue sections subjected to CD34 immunostaining and haematoxylin counterstain. CD34/CD31 double immunofluorescence was performed to unequivocally differentiate telocytes (CD34+/CD31-) from vascular endothelial cells (CD34+/CD31+). Quantitative analysis of telocytes was performed on tissue sections double-immunostained for CD34/CD31 and counterstained with DAPI for nuclei. Results: The histopathological examination of Masson's trichrome-stained sections showed the typical fibrotic changes of SSc. A generalized fibrosis affected all SSc gastric wall layers, with most severe changes in the muscularis mucosae, submucosa and muscularis propria. Few telocytes entrapped in the fibrotic extracellular matrix were found in the muscularis mucosae and submucosa. In the muscularis propria, the network of telocytes was discontinuous or even almost completely absent around smooth muscle bundles and cells, as well as around ganglia and nerve strands at the myenteric plexus. Wide areas of interstitial fibrosis and hypertrophy of cardiomyocytes were observed in SSc myocardium. In the fibrotic areas of SSc myocardium, telocytes were severely reduced or completely undetectable. Lung sections from SSc patients displayed the typical features of non-specific interstitial pneumonia with both diffuse cellular inflammation and collagen deposition resulting in thickening of alveolar septa and severe distortion of the pulmonary parenchyma structure. In SSc fibrotic lung, very few or no telocytes were found in the thickened alveolar septa, around blood vessels and in the interstitial space surrounding terminal and respiratory bronchioles. Quantitative analysis demonstrated a significant reduction in the number of telocytes in sections from SSc organs compared with the respective controls (all p<0.05). Conclusions: In SSc, the loss of telocytes is not restricted to the skin, but it is a widespread process affecting multiple organs targeted by the fibrotic process. As telocytes are believed to be key players in the regulation of tissue/organ homoeostasis, our data suggest that telocyte loss might have important pathophysiological implications in SSc. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2065